Non- Resonant Reaction Rate for 15N (p,γ)16O Reaction - Abd Ali, Fatimah Fadhil; Selman, Ahmed Abdul-Razzaq (Iraqi Journal of Physics, 2025)
Light isotopes, especially closed-shell nuclei, have significance in thermonuclear reactions of the Carbon-Nitrogen-Oxygen (CNO) cycle in stars. In this research, radiative proton capture of 15N(p,γ)16O was calculated using MATLAB codes to find the reaction rate across a temperature range up to 10 GK for the spectrum's non-resonant part, and the astrophysical S- factor S(E) only at low energies (E=70 keV). The findings were compared with conventional reactions before and after statistical analyses, and the results were acceptable when compared to earlier compilations and reference libraries. For temperatures 0.07 < T9 < 0.09, current direct data cover 50-90 % of the region under the Gamow peak. At T9 < 0.15, non-resonant capture becomes more important, and the current rate is up to 40 % lower than NACRE-II due to lower S factor values than the NACRE-II extrapolation. For energies E < 70 keV, a linear relationship for the S-factor was assumed.